2009
DOI: 10.4062/biomolther.2009.17.3.241
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Methylsulfonylmethane on Hair Growth Promotion of Magnesium Ascorbyl Phosphate for the Treatment of Alopecia

Abstract: Fig. 1. The chemical structures of magnesium ascorbyl phosphate (MAP) and methylsulfonylmethane (MSM). (A) Magnesium ascorbyl phosphate (MAP). (B) Methylsulfonylmethane (MSM).Abstract -The purpose of this study was to evaluate the effect of methylsulfonylmethane (MSM) on hair growth promotion of magnesium ascorbyl phosphate (MAP) for the treatment of alopecia. Aqueous solutions of MAP 7.5% with or without MSM 1%, 5% or 10% were prepared and applied onto the depilated back skin of the male mice once a day for 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Each of its components has been incorporated to potentially apply a multifaceted approach to the treatment of AGA (Table 1). Similarly, the formulation contains methylsulfomethane, designed to aid penetration of the active topical ingredients [32]. Since it is used as a topical formulation, it minimizes adverse or toxic effects that are sometimes experienced after the ingestion of botanical extracts.…”
Section: Discussionmentioning
confidence: 99%
“…Each of its components has been incorporated to potentially apply a multifaceted approach to the treatment of AGA (Table 1). Similarly, the formulation contains methylsulfomethane, designed to aid penetration of the active topical ingredients [32]. Since it is used as a topical formulation, it minimizes adverse or toxic effects that are sometimes experienced after the ingestion of botanical extracts.…”
Section: Discussionmentioning
confidence: 99%
“…The isolated fraction contains almost 81% of dimethyl sulfone. Shanmugam et al., 2009 have proved that dimethyl sulfone has been effectively used for the treatment of alopecia [ 43 ]. The effect of the BE alcoholic extract can be attributed to the presence of Dimethyl sulfone, which is the major constituent of the isolated fraction.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that magnesium supplementation may improve alopecia because previous studies showed that magnesium deficiency contributed to alopecia and disrupted cholesterol-enhanced hair loss [ 50 ]. Also, topical application of magnesium was reported to be effective in regrowth of shed hair in mice [ 51 ]. Nevertheless, a case–control study found that only protein intake was directly effective in alopecia compared to micronutrients including magnesium [ 52 ].…”
Section: Discussionmentioning
confidence: 99%